1993
DOI: 10.1121/1.407880
|View full text |Cite
|
Sign up to set email alerts
|

Current status of sleep disturbance research and development of a criterion for aircraft noise exposure

Abstract: There currently exists no generally accepted criterion for an acceptable level of nighttime sleep disturbance from aircraft noise. Indeed, there is little agreement concerning the appropriate scientific definition of sleep disturbance, the appropriate noise exposure metric for this environmental effect, or the circumstances under which such predictions need to be included in environmental impact analyses. However, with the large body of scientific evidence on sleep disturbance due to environmental noise that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The two exposure-response curves were adopted in 1992 by the Federal Interagency Committee on Noise 1 ͑FICON͒ for use by federal agencies in aircraft noise-related environmental impact analyses and are recommended for prediction of the effects of general transportation noise on people. The curves were described previously in general form [2][3][4] and have already been used in Environmental Impact Statements. 5 The recommendations in this paper are based on reanalyses of two sets of previously published data.…”
Section: Introductionmentioning
confidence: 99%
“…The two exposure-response curves were adopted in 1992 by the Federal Interagency Committee on Noise 1 ͑FICON͒ for use by federal agencies in aircraft noise-related environmental impact analyses and are recommended for prediction of the effects of general transportation noise on people. The curves were described previously in general form [2][3][4] and have already been used in Environmental Impact Statements. 5 The recommendations in this paper are based on reanalyses of two sets of previously published data.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, laboratory studies have shown considerably more disturbance than field studies [Pearsons, 1992]. Finegold speculates that the significantly greater awakening observed in the laboratory is due to the lack of habituation [Finegold, 1993].…”
Section: Study Design: Laboratory Vs Field Researchmentioning
confidence: 99%
“…This interim curve was based on statistical adjustment of Pearsons' 1989 analysis, and included data from both laboratory and field studies [Finegold, 1993]. The recommended dose-response relationship is shown in Figure 1, and can be expressed by the following equation:…”
Section: Ficon Sleep Disturbance Recommendationsmentioning
confidence: 99%